THE EFFECTS OF STORYTELLING TEACHING STYLE ON ELEMENTARY STUDENTS’ READING COMPREHENSION - Adelea La Bertha Santoso; Daniel Ginting; Wawan Eko Yulianto (Journal of English Educational Study (JEES), 2023)
This study explores the impact of the storytelling teaching style on the reading comprehension of elementary school students at the School of Life, GSJA El-Roy, Semarang. It was discovered that reading comprehension in English for elementary students in 5th and 6th grades was still too low, and students' reading skills still needed to be improved. In addition to improving reading skills, storytelling fosters critical thinking and helps children understand the order and structure of stories. To assess the effectiveness of the storytelling method in enhancing students' reading skills, the writer used Classroom Action Research (CAR) and set a success scale above 8.5, measuring students' reading comprehension using various English vocabulary. A test was administered to 10 students, and the results revealed an average success scale of 9.3, indicating a significant improvement in students' reading comprehension skills. The writer suggest that future research need to conduct a follow-up assessment after an extended period would allow researchers to determine the long-term effects of the storytelling-based teaching strategy on students' reading comprehension skills.Keywords: Storytelling teaching style, reading comprehension skills, classroom action research